Contemplating the role of zinc-solubilizing bacteria in crop biofortification: An approach for sustainable bioeconomy - Upadhayay, Viabhav Kumar; Singh, Ajay Veer; Khan, Amir; Sharma, Adita (Frontiers in Agronomy, 2022)
Modern agriculture pays attention to improve agricultural production by producing zinc-enriched crops through zinc-solubilizing bacteria (ZSB) to strengthen the bioeconomy. Zinc deficiency in the soil reduces plant growth and also leads to less uptake of zinc in the edible portion of plants. Therefore, the zinc content in edible parts of plants can be increased through the biofortification approach. But most of the biofortification approaches are laborious and need expensive input in routine practices. Therefore, the microbiological biofortification approach may be beneficial in increasing zinc concentration in plants and improving crop quality with the ultimate benefit of a greener path. Therefore, the use of microbes may be favorable for elevating zinc content in plants and enhancing crop quality, ultimately providing a summation of the role of microorganisms for a greener strategy. In addition, the application of zinc-solubilizing bacteria as a potential biosource represents a cost-effective and alternate biofortification strategy. Zinc solubilizing bacteria act as natural soil bio-fortifiers to solubilize the unavailable form of zinc by secreting organic acids, siderophores, and other chelating compounds. This review thus focuses on zinc- solubilizing bacteria for plant biofortification and their contribution to enhance crop yield and the bioeconomy in a more sustainable manner.